PENGARUH PERSEPSI HARGA, KUALIATAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI RICHEESE FACTORY JATIBENING BEKASI - Annastaya Putri; Bambang Nur Supriyanto (Human Capital Development, 2023)
This study hopes to analyze the impact of visible costs, product quality and area on purchasing choices in the Richeese Jatibening production line. This research example consists of 100 respondents who are restaurant owners. Information was collected using surveys and checked using various relapse investigation strategies. The results showed that the impression of cost, quality of goods and area as a whole influenced the purchase choice at Richeese Plant Jatibening. Buying choices also affect buyers.